PROSPECT OF THE COMMON CARP (Cyprinus carpio L.) CAGE CULTURE IN MURUNG RAYA REGENCY - Syafi’i, A. (The Journal is published by Graduate Programe of Lambung Mangkurat University, 2017)
This study aimed to (1) find out the water quality parameters of the river where the common carp cage cultures are located at Murung Raya Regency, either adjacent or far from the gold mine site, including water temperatures, pH, dissolved oxygen, carbon dioxide, ammonia and water clarity; (2) to compare the common carp cage culture profits in the river either adjacent or far from the gold mine sites; and (3) to determine the common carp cage culture development strategies at Murung Raya Regency. This study was carried out in Murung Raya Regency, Central Kalimantan, with the common carp cage farmers at Muara Supoi and Muara Bumban Villages, Murung Regency as the object. The collected data were primary and secondary data. The data analysis used were descriptive analysis, t statistical test, and a SWOT analysis. The results of the study showed that condition of the water where the common carp cage cultures are located at Murung Raya Regency, either adjacent or far from the gold mine sites, still in the range of the quality standards required, namely the temperature of 29.73 - 29.78oC; water clarity of 10 - 11 cm; pH of 6.58 - 6.65; dissolved oxygen of 6.11 - 6.73 mg /l; carbon dioxide of 0.02 - 0.03 mg/l; and ammonia of 0.02 mg/l, so that the common carp cage culture activities at Murung Raya Regency were still very feasible to carried on. The average profits of the common carp cage cultures, either adjacent or far from the gold mine sites, were relatively similar, with the t statistical test result showed that the profits at both locations did not differ significantly at 95% test level. The development strategy of common carp cage cultures at Murung Raya Regency was in quadrant II or S - T, namely utilizing the strengths to overcome the threats. It was implemented by establishing two alternative solutions, namely (1) by taking advantage from the fish culture development programs and supports by the government; and (2) optimized the development function of the of seed center for supplying the high-quality seeds. One of them was by utilizing the special allocation fund (Dana Alokasi Khusus - DAK) from the Ministry of Marine Affairs and Fisheries.